2020
DOI: 10.1093/neuonc/noaa050
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of an aggressive orthotopic murine glioblastoma model with combination checkpoint blockade and a multivalent neoantigen vaccine

Abstract: Background Although clinical trials testing immunotherapies in glioblastoma (GBM) have yielded mixed results, new strategies targeting tumor-specific somatic coding mutations, termed “neoantigens,” represent promising therapeutic approaches. We characterized the microenvironment and neoantigen landscape of the aggressive CT2A GBM model in order to develop a platform to test combination checkpoint blockade and neoantigen vaccination. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 54 publications
4
64
0
Order By: Relevance
“…Nonetheless, it seems clear that this basal immunogenicity alone is not able to make C57BL/6 mice resistant to GL261 GB growth, in the absence of IMS–TMZ therapy. It may be relevant to evaluate in future work whether less immunogenic models respond to IMS combined TMZ/anti PD-1, like the CT-2A model [ 44 ]. Moreover, other authors favour genetically engineered mice (GEM) models of GB, harbouring defined driver mutations leading to tumour progression [ 45 , 46 , 47 ], which are claimed to better reproduce human GB development.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it seems clear that this basal immunogenicity alone is not able to make C57BL/6 mice resistant to GL261 GB growth, in the absence of IMS–TMZ therapy. It may be relevant to evaluate in future work whether less immunogenic models respond to IMS combined TMZ/anti PD-1, like the CT-2A model [ 44 ]. Moreover, other authors favour genetically engineered mice (GEM) models of GB, harbouring defined driver mutations leading to tumour progression [ 45 , 46 , 47 ], which are claimed to better reproduce human GB development.…”
Section: Discussionmentioning
confidence: 99%
“…In syngeneic murine models of glioma, melanoma, sarcoma, and colorectal cancer, neoepitope vaccines (delivered with various adjuvants) induced robust antigen-specific IFNγ responses in CD4 and CD8 T cells. This resulted in decreased tumor [14,[18][19][20][21][22]. Tumor growth control was associated with increased infiltration of anti-tumor immune cells and decreased suppressive cells in the tumor microenvironment [14,19].…”
Section: Neoepitopes As Monotherapy Vaccinesmentioning
confidence: 99%
“…Additionally, it is important to rationally select agents for combination and to ensure that agents do not antagonize each other. Due to promising results from monotherapy vaccine studies targeting neoepitopes, recent preclinical studies investigated combining neoepitope vaccines with other cancer therapies, including checkpoint inhibitors [18,20,28,[30][31][32][33], other immunooncology agents [18,34], and "non-immune" therapies [35] to improve their efficacies. Additionally, numerous clinical trials, summarized in Table 1, have been proposed to investigate neoepitope vaccination in combination with checkpoint inhibitors, other immuno-oncology agents, and "non-immune" cancer therapies.…”
Section: Neoepitopes In Combination Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…T cells specific for neoantigenic peptides are not attenuated by immune tolerance mechanism and do not harm healthy tissues (1). Recent clinical trials have shown that de novo immune responses can be induced by vaccination with neoantigens in melanoma and glioblastoma patients (2)(3)(4)(5). The optimal peptide length for therapeutic cancer vaccines has been identified in preclinical and clinical studies.…”
Section: Introductionmentioning
confidence: 99%